Kepemimpinan yang inspiratif: Membangun motivasi karyawan di bank syariah - Octavia, Irene Hevy (Maliki Interdisciplinary Journal, 2024)
Inspirational leadership plays an important role in increasing employee motivation, especially in the Islamic banking sector which emphasizes ethical values ​​and integrity. This article discusses how inspiring leaders can influence employees’ intrinsic and extrinsic motivation, and their impact on organizational performance. Through a qualitative or literature approach, this article explores the characteristics of inspirational leaders, effective communication strategies, and employee feedback and development practices. In addition, this article also identifies the challenges faced in implementing inspirational leadership in Islamic banks, including cultural barriers and resource constraints. By integrating Islamic values ​​into leadership practices, Islamic banks can create a positive and productive work environment. These findings are expected to provide insights for leaders in the Islamic banking sector to improve employee motivation and performance sustainably.